Determination of transfer coefficients of a tunnel type screenhouse for thermal modelling. Issue 1 (July 2020) - Muhammad, F; Suhardiyanto, H
Abstract: Screenhouses could help the reduction of pesticide usage for sustainable agriculture production in the tropics. A screenhouse is inherently naturally ventilated by the air flowing through the screen that covers the structure. However, overheating is still a problem that often occurs inside screenhouses in the tropics. Therefore, it is important to develop a thermal model as design tool for tropical screenhouses. The objective of this study was to determine the screenhouse transmissivity and the overall heat transfer coefficient of a tunnel type screenhouse for thermal modelling. A thermal model has been developed to consider these transfer coefficients. The model was modified from thermal model proposed by Desmarais et al. Validation of the thermal model was done by comparing predicted air temperature inside the screenhouse to that of measured values. The average transmissivity of the screenhouse obtained was 0.42, while the heat transfer coefficient of the screenhouse averaged from measurement results was 51.6 W/m 2 o C. The validation showed that predicted air temperature inside the screenhouse agreed well to that of the measured values. It was concluded that the thermal model could be used as a good design tool for tunnel type tropical screenhouses.